1993
DOI: 10.1042/bj2950011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell volume on Acridine Orange fluorescence in hepatocytes

Abstract: Hepatic proteolysis is inhibited by cell swelling following a variety of experimental manoeuvres, such as reduction of extracellular osmolarity, concentrative uptake of amino acids, or blockade of K+ channels by barium. On the other hand, proteolysis is known to be accomplished by pH-sensitive lysosomal proteases. Accordingly, NH3/NH4+ inhibits proteolysis by intralysosomal alkalinization. The present study has been performed to test for an effect of cell volume on the pH of acidic intracellular compartments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…The present observations confirm previous studies demonstrating that osmotic cell swelling increases the apparent vesicular pH as calculated using FITC-dextran and triggers release of acridine orange from acidic vesicles (3,17,18). Alkalinization of acidic vesicles is expected to increase the fluorescence ratio of FITC-dextran, which remains trapped within vesicular compartments, including endosomes and lysosomes, after being endocytosed (14).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present observations confirm previous studies demonstrating that osmotic cell swelling increases the apparent vesicular pH as calculated using FITC-dextran and triggers release of acridine orange from acidic vesicles (3,17,18). Alkalinization of acidic vesicles is expected to increase the fluorescence ratio of FITC-dextran, which remains trapped within vesicular compartments, including endosomes and lysosomes, after being endocytosed (14).…”
Section: Discussionsupporting
confidence: 80%
“…The mechanism linking cell volume alterations to proteolysis remained elusive, however, until recently when it was observed that cell swelling leads to an increase in acridine orange fluorescence intensity. This effect indicated an alkalinization of acidic intracellular compartments (3). Since proteolysis resides largely within acidic lysosomes and is accomplished by pH-sensitive lysosomal proteinases (4), the alkalinization of acidic intracellular compartments could indeed couple cell swelling to the inhibition of proteolysis.…”
mentioning
confidence: 99%
“…A decrease of extracellular osmolarity leads to osmotic cell swelling, which modifies a variety of cellular functions, such as transport, metabolism, cell proliferation, and cell death (for a review, see reference 27). Most notably, it is well established that cell swelling results in alkalinization whereas cell shrinkage results in acidification of endosomal pH (10)(11)(12)(13)(14)(15)(42)(43)(44). Previous investigations have shown that, due to inhibition of the fusion of the phagosome and lysosome, the phagosome of L. pneumophila does not become acidified (25,26,38) and therefore enables the intracellular multiplication of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been presented for a direct activation of the vesicular proton pump by Cl - (58) , independent of the role of chloride channels in shunting the endosomal membrane potential, which is generated by the proton pump. A hyperosmolarity-induced increase of the cytosolic chloride concentration may thus indirectly augment vesicular acidification, whereas a decrease in cytosolic chloride could explain the vesicular alkalinization, which is observed in response to cell swelling (64) . Regardless, the mechanisms underlying the osmo-sensitivity of endosomal pH, modulation of endosomal pH must be seen as one site of hepatocellular osmo-sensing through the modulation of acidic sphingomyelinase (ASM) activity and subsequent ceramide formation, which have been described as a downstream consequence of endosomal acidification in this experimental setting (56) .…”
Section: Downstream Dual Activation Of Both Erks and P38mentioning
confidence: 99%